Kinetic and diffusive data from batch combustion of wood chars in fluidized bed - Rangel, N; Pinho, C (Biomass and Bioenergy, 2011)
In this work it is studied the combustion of batches of wood char particles in a shallow ﬂuidized bed at laboratory scale. Commercial and recarbonized chars from nut pine and cork oak parent woods were burned for bed temperatures of 600e750 C and particle sizes range of 1.8e3.6 mm. A combustion model based on the two-phase theory of ﬂuidization is presented to evaluate the global combustion resistance. Sherwood numbers and kinetic constants for the heterogeneous phase reaction are also assessed. Through the comparison among theoretical and experimental results, conclusions are drawn on the combustion mechanism as well as on the combustion controlling resistance. The Arrhenius law is proposed to predict the kinetic constants for the studied chars
Keywords: Experimental data; Fluidized bed combustion; Kinetic constant; Modeling; Wood char